Electric condensation and dehydration of red sludge - Разгонова, Олеся Віталіївна; Сокольник, Володимир Іванович (Eastern-European Journal of Enterprise Technologies, 2014)
Red sludge is a mixture resulting from production of aluminum with high content of iron and aluminum oxides. Through lack of effective technologies for processing and high moisture, a bulk of red sludge is not utilized. Instead, it is stocked in huge sludge fields with an obvious alkaline environment, which is fatal to anything living on earth. There are methods of processing red sludge, such as sedimentation, filtering, drying, pyrometallurgical processing, magnetic separation, recuperative melting, hydrometallurgical schemes, etc. Most of these methods, however, are not really used because of their being economically and technically inefficient. The study is focused on the method of condensation and dehydration of red sludge in the electric field. The method does not require huge investments and allows using dehydrated red sludge as a valuable raw material in various industries. The researched red sludge suspension was taken from the sludge storage at Zaporizhzhya Aluminum Plant. The research was conducted in on the designed laboratory equipment consisting of two cylinders. One of the cylinders was equipped with electrodes supplying electric voltage from 0 V to 175 V, while the other showed gravitational sedimentation. The obtained graphical dependence proved that the smallest fraction of 28 % of sludge sediment was received with electric voltage of 150 V, whereas the fraction of sludge sediment without exposure to electricity was 45 %. Voltage supply of 25 V resulted in the longest 260-minute condensation, and with supply of 175 V the condensation process was the shortest—90 minutes. The obtained findings showed that electric-field condensation and dehydration of red sludge can facilitate condensation and reduce the volume fraction of sludge sediment. The advantage of the method is condensation and dehydration of red sludge within short time with reduced energy costs. Application of the suggested method in aluminum production will reduce the production pressure on the environment.